HOXB9 acetylation at K27 is responsible for its suppression of colon cancer progression. (10th July 2018) - Song, Jiagui; Wang, Tianzhuo; Xu, Weizhi; Wang, Peng; Wan, Junhu; Wang, Yunling; Zhan, Jun; Zhang, Hongquan
Abstract: We previously reported that HOXB9 is overexpressed in colon cancer and predicts a favourable patient outcome, which is opposite to the tumour-promoting role of HOXB9 in other cancers. We hypothesized that HOXB9 acetylation may account for its inhibitory role in colon cancer. We aim to examine the role of acetylated HOXB9 in colon cancer cells and patients. The AcK27-HOXB9 levels in colon cancer cells and patients were analysed by Western blot analysis and immunohistochemistry separately. Correlation between AcK27-HOXB9 expression and patient survival was assessed by Kaplan–Meier analysis. HOXB9 target gene EZH2 was determined by luciferase assay in HOXB9-transfected colon cancer cells. Nucleocytoplasmic translocation of HOXB9 was detected by subcellular fractionation and immunofluorescence. The AcK27-HOXB9 level was decreased in colon cancer patients and predicted better outcome. HOXB9 upregulated oncogenic EZH2 expression, whereas AcK27-HOXB9 suppressed it by translocating HOXB9 from nuclei into cytoplasm. We demonstrated that AcK27-HOXB9 inhibits while non-acetylated HOXB9 promotes EZH2 expression and colon cancer progression. Thus, AcK27-HOXB9 underlies the tumour suppressive role of HOXB9. Detection of the ratio between AcK27-HOXB9 and HOXB9 is of differential diagnostic value for colon cancer patients. Highlights: HOXB9 acetylation at K27 is downregulated in colon cancer patients and predicts a favourable outcome. HOXB9 targets to and upregultes EZH2, while AcK27-HOXB9 alleviates this effect. Acetylated HOXB9 translocates from nucleus to cytoplasm and plays a role in suppression of colon cancer.